2022
DOI: 10.4103/jos.jos_22_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation and influence of new Optibond eXTRa self-etch Universal adhesive and conventional Transbond XT on shear bond strength of orthodontic brackets—An in vitro study

Abstract: INTRODUCTION: The demand by dental practitioners for adhesives led to the innovation of newer self-etched universal adhesive systems. The objectives were to evaluate the shear bond strength (SBS) of metal brackets bonded with Optibond eXTRa Universal self-etch adhesive and Transbond XT primer and also to assess the adhesive remnant index (ARI). MATERIALS AND METHODS: A total of 100 extracted human premolar tooth samples were divided into 2 groups (n = 50) according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This adhesive provided a stronger adhesion than a conventional adhesive. [33][34][35][36][37] Finally, all the groups tested in our study had bond strength values well above the minimum needed for bonding orthodontic brackets as de ned by Reynolds 3 (between 5.9 and 7.8 MPa); therefore, they were clinically applicable for the three materials evaluated.…”
Section: Sbs Values Obtainedmentioning
confidence: 94%
See 3 more Smart Citations
“…This adhesive provided a stronger adhesion than a conventional adhesive. [33][34][35][36][37] Finally, all the groups tested in our study had bond strength values well above the minimum needed for bonding orthodontic brackets as de ned by Reynolds 3 (between 5.9 and 7.8 MPa); therefore, they were clinically applicable for the three materials evaluated.…”
Section: Sbs Values Obtainedmentioning
confidence: 94%
“…32 Contrary to conventional self-etching adhesives, universal adhesives provided micromechanical and chemical adhesion by the interactions of functional monomers with the calcium of hydroxyapatite, which could explain the increase in the SBS values obtained. [33][34][35][36] For the groups using TXT, the application of a universal adhesive after enamel etching signi cantly increased the SBS values (29.30 MPa for Group 9 (H 3 PO 4 + SU + TXT) vs. 19.38 MPa for Group 6 (TSEP + TXT) and 21.6 MPa for Group 8 (SU + TXT)). These results agreed with those of several authors who have shown an increase in the adhesion value with acid etching prior to the application of a universal adhesive but no signi cant difference between the application of a conventional self-etching system and a universal adhesive without prior etching.…”
Section: Sbs Values Obtainedmentioning
confidence: 99%
See 2 more Smart Citations
“…In restorative dentistry, authors showed a high SBS value with acid etching and universal adhesive application prior to the application of a RMGIC on composite resin or dentin [35]. Contrary to conventional self-etching adhesives, universal adhesives provided micromechanical and chemical adhesion by the interactions of functional monomers with the calcium of hydroxyapatite, which could explain the increase in the SBS values obtained [36][37][38][39].…”
Section: Sbs Values Obtainedmentioning
confidence: 99%